Degradation Fermented Feed Animal Based Local Mikroorganism To Increased Nutrient Quality Of The Waste Gambir Fermented - Roni Yulianto; Gusna Merina; Lanang Nashrullah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2022)
The efforts to reduce production costs to minimize feed costs, so that farmers can benefit from livestock business. One way to meet the availability of feed ingredients quality and quantity as feed animal. The materials and tools used in this study were gambir extraction waste, local microorganism, rice washing water, fine bran, rumen microbes, Mc Dougall buffer solution, fermentation rack, salt, brown sugar, plastic and a set of tools for in-vitro testing. The study was conducted experimentally with a 3x4 factorial Randomized Block Design pattern with two replications for each treatment combination. Based on statistical analysis, it was shown that the use of bran and fermentation time had an insignificant (P>0.05) effect on Crude Protein (CP) degradation in the rumen in vitro and a very significant (P<0.01) effect on NH3 production, Crude Fiber (CF) Degradation and volatile fatty acid Production. The results of study was that leg fermented with local microorganisms showed no significant difference in CP degradation, while NH3 production. CF degradation and volatile fatty acid production increased from leg fermented with local microorganisms without the addition of bran, so it could be used as feed ruminant.